THE EXONERATION CLAUSES IN PARKING PRACTICES: A REVIEW FROM THE PRINCIPLE OF PROPORTIONALITY AND INCLUSIVE LAW - Simbolon, Herbert Petrus Wiro; Kurniawan, I Gede Agus (JCH (Jurnal Cendekia Hukum), 2023)
This research focuses on the analysis of exoneration clauses in parking practices from the perspective of proportionality and inclusive law perspectives. This research is a normative legal research with a concept, case, and statutory approach. The results of the study confirm that exoneration clauses in parking practices are usually not in accordance with the principle of proportionality because they ignore the substance in various court decisions where one of the substances is the exoneration clause should not be a means to "escape" from the responsibility of the parking manager because as stated in MA Decision No. 3416/Pdt/1985 parking practices are constructed as goods safekeeping agreements and the existence of an exoneration clause does not eliminate the responsibility of the parking manager to safeguard the goods deposited as long as it can be proven without any intention or negligence by the parking manager. Therefore, in the future the principle of proportionality can serve as a guide as well as a tester for the substance of the exoneration clause in parking practices. Furthermore, an inclusive legal perspective with regard to exoneration clauses in parking practices, in fact, exoneration clauses in parking practices is contrary to the spirit of prophetic law which emphasizes balanced legal relations and relations between parking managers and parking users as consumers. For this reason, to overcome the existence of an exoneration clause in parking practices is to involve the role of the regions in formulating a Regional Regulation which states that the exoneration clause in parking practices with the substance of business actors, namely the parking manager, is not responsible for losses suffered by consumers, namely parking users, is null and void by law. and can be accompanied as in the provisions of the PK Law.